2005
DOI: 10.1091/mbc.e05-03-0194
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of the Ubiquitin Ligase Activity of UHRF1, a Nuclear RING Finger Protein, in Tumor Cell Growth

Abstract: Early cellular events associated with tumorigenesis often include loss of cell cycle checkpoints or alteration in growth signaling pathways. Identification of novel genes involved in cellular proliferation may lead to new classes of cancer therapeutics. By screening a tetracycline-inducible cDNA library in A549 cells for genes that interfere with proliferation, we have identified a fragment of UHRF1 (ubiquitin-like protein containing PHD and RING domains 1), a nuclear RING finger protein, that acts as a domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
152
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(176 citation statements)
references
References 29 publications
11
152
1
Order By: Relevance
“…This suggests that pathological overexpression of UHRF1, by repressing permanently the expression of specific tumor suppressor genes, could induce disorders in the G1/S progression and consequently promote tumor development [10]. In agreement with our hypothesis, it has been shown that the activation of different cell cycle checkpoints during DNA damage-induced apoptosis leads to a down-regulation of UHRF1 [9]; such deregulation has been described to be dependent on the p53/p21 WAF1/CIP1 pathway [14]. It should be noted that reduction of UHRF1 expression solely can suppress proliferation and induce apoptosis of cancer cells whose p53 is inactivated [15].…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…This suggests that pathological overexpression of UHRF1, by repressing permanently the expression of specific tumor suppressor genes, could induce disorders in the G1/S progression and consequently promote tumor development [10]. In agreement with our hypothesis, it has been shown that the activation of different cell cycle checkpoints during DNA damage-induced apoptosis leads to a down-regulation of UHRF1 [9]; such deregulation has been described to be dependent on the p53/p21 WAF1/CIP1 pathway [14]. It should be noted that reduction of UHRF1 expression solely can suppress proliferation and induce apoptosis of cancer cells whose p53 is inactivated [15].…”
Section: Introductionsupporting
confidence: 85%
“…The consequences of this hypermethylation and its maintenance are not clearly understood but they likely target the expression of specific genes involved in the DNA damage response. We hypothesized that UHRF1 (Ubiquitin-like, containing PHD and RING Finger domains, 1) could be a major effector of the p73 deregulation, since this nuclear protein is known to be over-expressed in numerous cancer cell lines and tissues [8][9][10][11]. 4 Several studies have shown that UHRF1 participates in the control of cell proliferation and cell cycle transition from G1 to S, by regulating the expression of several genes, including RB1 and p16 INK4A [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the reported association between UHRF1, proliferation, 30 and tumor cell growth. 44 E2F1 levels did not change upon UHRF1 knockdown, indicating a lack of a feedback loop. Both our ex vivo and in vitro data suggest that UHRF1 can influence the cell cycle control mainly through the epigenetic silencing of relevant tumor suppressors.…”
Section: Discussionmentioning
confidence: 89%
“…UHRF1 mRNA was overexpressed in NSCLC tumor tissues in comparison to their normal adjacent tissue, confirming in a large sample set a preliminary observation. 44 UHRF1 overexpression was more profound in squamous carcinomas than adenocarcinomas, further underlying the differences in the molecular evolution of these tumor types. Further research is required to provide evidence on whether this difference could be used in the clinical management of these 2 histological types.…”
Section: Discussionmentioning
confidence: 99%